2000
DOI: 10.1080/026990500445736
|View full text |Cite
|
Sign up to set email alerts
|

Injury severity and neuropsychological and balance outcomes of four college athletes

Abstract: Recent evidence suggests significant short-term neurocognitive deficits following mild traumatic brain injury (MTBI) in sports. However, sequelae of mild head injuries is complicated by many factors including a history of multiple head injuries and injury severity. Few studies have considered the influence these variables may have on proper classification of a MTBI and their meaning for return-to-play guidelines. This study presents the short-term neuropsychological and balance outcomes of four college athlete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is one of several recommended tools for determining readiness to resume competitive activity among athletes [16]. Previous research has suggested that athletes with postural instability after concussion return to their baseline levels of postural steadiness performance within about 3 days often despite still being symptomatic [17]–[20]. This suggests that either (a) neurophysiological impairments affecting postural control are not necessarily a predictable consequence of injury, or (b) more sensitive analyses of postural instability may be required.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of several recommended tools for determining readiness to resume competitive activity among athletes [16]. Previous research has suggested that athletes with postural instability after concussion return to their baseline levels of postural steadiness performance within about 3 days often despite still being symptomatic [17]–[20]. This suggests that either (a) neurophysiological impairments affecting postural control are not necessarily a predictable consequence of injury, or (b) more sensitive analyses of postural instability may be required.…”
Section: Introductionmentioning
confidence: 99%
“…This may have been caused by the punches to the head area received by the boxers during the match. Mrazik et al (2000), in their research conducted for college athletes at the University of Georgia, included athletes with a high risk of concussion in their study. As a result, it was determined that the SDMT performances of athletes with a higher number of concussions were poor.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of postural control after a concussion often highlight transient deficits in an individual's ability to integrate the sensory components necessary for maintaining balance. 3,4 Sensory integration and balance deficits have been reported among concussed athletes, [5][6][7] and collectively suggest that brain regions responsible for coordinating sensory and vestibular modalities may be disrupted following sport-related concussion. 8 Making accurate evaluations of balance disturbances post-injury may be compromised without an accurate preinjury comparison.…”
Section: Introductionmentioning
confidence: 99%